Indonesia's Sustainable Fisheries Agenda: From Policy to Practice of Indonesian National Plan of Action - Rizki Apriliana, Adhitya Nini (JATISWARA, 2024)
There remain unanswered questions regarding practice of illegal fishing in Indonesia which two-folding the poses of significant threat to its biodiversity and contributes to the overexploitation of fisheries resources. Not only grapples with the imbalance between the abundant fishing potential, this practice indeed fundamentally encompasses various other violations beyond just the act of stealing fish. In order to address these pressing challenges, Indonesia has taken steps to optimize its national marine and fisheries resources. As a member of the 2007 RPOA-IUU, it shortly become matter of concern to this diverse archipelago with over 17.000 islands in Southeast Asia to then embraced the establishment of its National Plan of Action as a means to combat illegal fishing practices in the country's waters. After being implemented for almost a decade, the practice of illegal fishing still continues to occur. This socio-legal research questioning the real effectiveness of Indonesian National Plan of Action in combating illegal fishing. Through the combination of statute approach and conceptual approach, it analyses how this national instrument aligns with the Fisheries Legislation Model to address illegal fishing on national level. From this point onwards, it is known that this phenomenon are supported by the lack of fundamental things in fishing activities such as engine fuel, fishing gear, boat engines, supplies, and logistics are still difficult for fishermen to access. Likewise, fishermen in Indonesia still need a transfer of knowledge, especially related to the use of e-logbooks that are still minimal in Indonesia.